Treatment Strategies to Manage Bronchitis of HMPV Origin, Through Homeopathy (Homoeopathy for All, 2025)
Human metapneumovirus (hMPV) is a recently identified human respiratory pathogen. Genetically, hMPV is closely related to avian pneumovirus and is classified within the subfamily Pneumovirinae, genus Metapneumovirus. The virus was first isolated in the Netherlands from 28 young children exhibiting illnesses similar to those caused by human respiratory syncytial virus (hRSV). Since its discovery, hMPV has been recognized as a significant cause of respiratory illnesses worldwide, particularly affecting young children, the elderly, and immunocompromised individuals. Symptoms are similar to those of other respiratory viral infections, ranging from mild (cough, rhinorrhoea, and fever) to more severe (bronchiolitis and pneumonia).
Keywords: Metapneumovirus; discovery; hMPV; immunocompromised